Tingkat Pendidikan PUS Berhubungan dengan Pemilihan Jenis Alat Kontrasepsi tetapi Tidak Berhubungan dengan Keikutsertaan KB di Desa Argomulyo, Sedayu, Bantul, Yogyakarta - Beyna Handayani; Nur Indah Rahmawati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2016)
Data of community practices in 2013 at the Argomulyo village known that total of reproductive age couples were 900 couples and 533 couples (59,22%) following family planning (FP). The purpose of this study was to know the relationship between the education level of reproductive age couples with FP participation and selection of contraceptives on reproductive age couples in the Argomulyo village, Sedayu, Bantul Yogyakarta. The study design was observational analytic with the cross sectional. The total population of reproductive age couples in hamlet of Kemusuk Kidul, Karang lo, Pedes, Surobayan, Kali Berot in the Argomulyo village, Sedayu Bantul were 916 couples. Samples were selected by total sampling technique which consisted of 907 couples and 9 couples included in the exclusion criteria. Data analysis was done by chi-square test. The results showed that 610 couples (67,3%) was following FP and 297 couples (32,7%) not following FP programs. The results of chi-square x2 of wife participation was 3,658 and selection of contraceptives was 50,194, x2 of husband participation was 0,926 and selection of contraceptives was 53,862. In conclusion, there was no relationship between the education level of reproductive age couples with FP participation and there was a relationship between the education level of reproductive age couples with selection of contraceptives in Argomulyo village, Sedayu, Bantul, Yogyakarta.